1979
DOI: 10.1210/jcem-48-1-92
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin-Cortisol Axis Abnormalities in Hemodialysis Patients*

Abstract: The ACTH-cortisol axis was studied in 15 hemodialysis patients. Basal plasma cortisol concentrations were found to be elevated and ACTH to be in the high normal range. Cortisol responded normally to exogenous ACTH, but neither cortisol nor ACTH were suppressed in response to oral dexamethasone. 11-Deoxycortisol and ACTH concentrations did not rise normally in response to either oral or iv metyrapone. We conclude that standard testing of the ACTH-cortisol axis in dialysis patients yields results suggesting Cush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1
3

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 0 publications
6
30
1
3
Order By: Relevance
“…Baseline cortisol levels in dialysis patients have been noted to be elevated in some studies [4, 7], but normal in others [3, 6, 13, 14, 15]. In our study, we found no significant difference in baseline cortisol levels between the dialysis and control groups regardless of the method utilized to measure cortisol.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Baseline cortisol levels in dialysis patients have been noted to be elevated in some studies [4, 7], but normal in others [3, 6, 13, 14, 15]. In our study, we found no significant difference in baseline cortisol levels between the dialysis and control groups regardless of the method utilized to measure cortisol.…”
Section: Discussioncontrasting
confidence: 50%
“…Others [5]have suggested that intravenous dexamethasone may be more effective than oral dexamethasone in patients on hemodialysis. Some investigators [6, 7, 8]have suggested that a higher oral dose of dexamethasone be used for testing in renal failure patients. Abnormalities in dexamethasone absorption have been implicated by some [6], but shown to be normal by others [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Moreover, at least half of this peripherally produced estrone is eventually converted to estradiol in extraovarian tissue. 28 Testosterone is the precursor of estradiol produced in the ovary by the cholesterol metabolism pathway. It accumulates after menopause with the loss of the ovarian function.…”
Section: Discussionmentioning
confidence: 99%